Análise dos livros didáticos utilizados no 8º e 9º ano do ensino fundamental: abordagem das doenças sexualmente transmissíveis (DST’s) - Iesbik, Simone Aparecida (2019)
This course was designed to analyze the textbooks of Fernando Gewandsznajder's eighth and ninth grade Teláris Project, and to verify if this material contemplates what is presented in the National Curricular Parameters (PCNs) on Sexually Transmitted Diseases. Sex education is understood as a set of information about sexuality, which is often treated informally, also occurring in the family environment, and is sometimes presented to young people as a moral standard imposed by society. The research was conducted in order to draw a comparative picture of what is predicted in PCNs regarding sexually transmitted diseases, and what is being addressed in the textbooks teachers are using in the classroom. We used bibliographical research and the use of the content analysis methodology for the interpretation of the research data. In the formal environment, in the case, the school, the research pointed out that it is presented in a superficial way. Through this study it can be concluded that it is possible to develop referrals in order to implement the actions of the teachers in relation to the subject, both with regard to work with students and parents.